2018
DOI: 10.1038/s41388-018-0593-5
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Gas6 promotes the progression of premalignant mammary cells

Abstract: Tumor progression is regulated by a complex interplay between neoplastic cells and the tumor microenvironment. Tumor associated macrophages have been shown to promote breast cancer progression in advanced disease and more recently, in early stage cancers. However, little is known about the macrophage-derived factors that promote tumor progression in early stage lesions. Using a p53-null model of early stage mammary tumor progression, we found that Gas6 is highly expressed in pre-invasive lesions associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 54 publications
2
35
0
1
Order By: Relevance
“…Several studies have aimed at macrophage‐derived factors that promote tumor progression in early lesions, confirming the role of macrophages in early cancer invasion (Gomes et al, ). Also, macrophages enhance the influx of cancer cells and induce Ras homolog gene family, member A activity in cancer cells during physical contact (Roh‐Johnson et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have aimed at macrophage‐derived factors that promote tumor progression in early lesions, confirming the role of macrophages in early cancer invasion (Gomes et al, ). Also, macrophages enhance the influx of cancer cells and induce Ras homolog gene family, member A activity in cancer cells during physical contact (Roh‐Johnson et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…GAS6 (growth arrest‐specific gene 6) is a cytokine and also a ligand for receptor tyrosine kinases, including TYRO3, AXL, and MERTK (TAM), which are well‐known pro‐survival signals in many cancers . In this study, we found that via increasing GAS6 expression, GAS6‐AS2 promoted the secretion of GAS6 in the cell supernatants, and further increased the phosphorylation levels of AXL, AKT, and ERK in an autocrine manner.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, GAS6‐AS2 was reported to activate GAS6 expression . GAS6 is a ligand for AXL receptor tyrosine kinase, which further activates downstream pro‐survival signals . Therefore, GAS6 has been revealed to have oncogenic roles in many cancers .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas6 is a multifunctional protein that is secreted by different cell types. Gas6 has been shown to be produced by macrophages in pre-malignant lesions of a mammary tumor model [28] and in xenograft and orthotopic models of colon and pancreatic cancer [29]. Gas6 can also be produced by tumor cells [30] and fibroblasts [31].…”
Section: Resultsmentioning
confidence: 99%